2008
DOI: 10.1007/s00425-008-0813-2
|View full text |Cite
|
Sign up to set email alerts
|

Feminized tassels of maize mop1 and ts1 mutants exhibit altered levels of miR156 and specific SBP-box genes

Abstract: Development of the unisexual maize inflorescences requires the abortion of pistillate primordia in the florets of the developing tassel and the arrest of staminate primordia in the florets of the developing ears. Mutations of many genes that lie within this sexual differentiation pathway, such as tasselseed1 (ts1), or that influence this pathway, such as mediator of paramutation 1 (mop1), result in feminization of the normally male tassel. Here, we show the loss of mop1 or ts1 function results in increased mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 57 publications
0
62
0
1
Order By: Relevance
“…Interesting in this context is that both miR156/7-targeted and nontargeted SBP-box genes, which according to our data regulate anther development similarly and as early as SPL/NZZ, are well conserved between monocots and dicots (Xie et al, 2006;Riese et al, 2007;Hultquist and Dorweiler, 2008). It would thus be interesting to determine if SBP-box genes play an evolutionarily more conserved role in sporogenesis.…”
Section: Mir156/7-targeted Spl Genes Are Required For Sporogenous Celmentioning
confidence: 62%
“…Interesting in this context is that both miR156/7-targeted and nontargeted SBP-box genes, which according to our data regulate anther development similarly and as early as SPL/NZZ, are well conserved between monocots and dicots (Xie et al, 2006;Riese et al, 2007;Hultquist and Dorweiler, 2008). It would thus be interesting to determine if SBP-box genes play an evolutionarily more conserved role in sporogenesis.…”
Section: Mir156/7-targeted Spl Genes Are Required For Sporogenous Celmentioning
confidence: 62%
“…In Arabidopsis, two miRNA species (20 and 21 nt) are observed for miR156 from shoot apices (37). In maize, a single miRNA species has been reported for miR156 (35,38), but its specific size was not reported. We found that similar to Arabidopsis, two size classes of miR156 can be observed in maize.…”
Section: Resultsmentioning
confidence: 97%
“…As previously described, eight SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE (SPL) transcripts targeted by the juvenile-stage regulatory RNA miR156 were upregulated in the L14 stage and lateral meristems (see Supplemental Data Set 14 online) (Chuck et al, 2007;Hultquist and Dorweiler, 2008;Strable et al, 2008). In addition, GLOSSY15 (GL15), an AP2-like transcription factor that promotes the adult leaf identity, is upregulated in 14-d-old seedlings (Evans et al, 1994;Moose and Sisco, 1996;Lauter et al, 2005).…”
Section: Comparative Transcriptomic Analyses Of Juvenile Adult and mentioning
confidence: 91%
“…A complex interactive network of phase-specific transcription factors and regulatory small RNAs regulate vegetative and reproductive phase change in plants (Moose and Sisco, 1996;Lauter et al, 2005;Chuck et al, 2007;Hultquist and Dorweiler, 2008). To examine the transcriptional differences among juvenilestage SAMs, adult-stage SAMs, and lateral shoot meristems from adult nodes on a genomic scale, the SAM and youngest leaf primordium were microdissected from L1-stage embryos and L14-stage seedlings, and lateral meristems were isolated from L14-stage seedlings.…”
Section: Comparative Transcriptomic Analyses Of Juvenile Adult and mentioning
confidence: 99%